Mass transfer coefficients of carbon dioxide in aqueous blends of monoethanolamine and glycerol using wetted-wall column - Babamohammadi, S.; Rozita, Y.; Aroua, M. Kheireddine *; N.Borhani, Tohid (Elsevier, 2021)
There is an urgent need for CO2 capture development because of the global warming crisis. Recently CO2 absorption by the mixture of monoethanolamine (MEA) and glycerol, as an eco-friendly solvent, has been considered due to its promising performance and low technical and environmental impacts. However, more aspects of this process, especially mass transfer coefficients, need to be studied further. In this work, a bench-scale wetted-wall column was used to find the CO2 mass transfer coefficients in the aqueous blends of MEA (25 wt%) and glycerol (5–20 wt%). The experiments were performed nearly to the industrial conditions of flue gas at atmospheric pressure and three different temperatures (313, 323, and 333 K). The gas flow rate was maintained around 0.17 ± 0.01 stdL/s, and the CO2 partial pressure was in the range of 1–15 kPa. The findings revealed that increasing the glycerol to 10 wt% improves the overall mass transfer (), and adding more glycerol up to 20 wt% decreases the . The gas-side mass transfer resistance () found to be negligible. Thus, the primary mass transfer resistance was in the liquid phase. It is also found that the solution with 10 wt% glycerol and 25 wt% MEA (10G25M) had the highest liquid-side mass transfer coefficient () among the other solutions. The 10G25M showed a comparable and even better absorption rate than solutions with a higher concentration of MEA studied in the literature. Compared with industrial-grade, the of the 10G25M was over two times higher than the 30 wt% MEA solution.